Documentary films in teaching Philippine history effects on pupil achievement - Ella, Merlinda B. (2009)
This research was conducted to explore the use documentary films in teaching Philippine History at the elementary school level. The classic pretest-posttest controlled group design was conducted with 2 groups of Grade 5 pupils. Lessons were concretized with materials and visual arts with substantial information and knowledge derived from various sources. It was revealed that audio-visual aids, such as documentary films, constituted innovations in teaching Philippine History and greatly improved instruction. Pupils from the treatment group performed better in application and analysis and had higher achievement than the control group. Thus, documentary films could be utilized regularly in teaching Philippine History and other related subjects to develop students' knowledge and skills.